DYNAMICS OF FISCAL POLICY IN THE ERA OF THE PROPHET SAW AND TRANSFORMATION IN FISCAL POLICY IN INDONESIA - Miftakhul Fauziyah Khasanah; Frida Eka Ristanti; Muhamad Aqim Adlan; Muhammad Aswad (Nurul Jadid University, 2026)
This study aims to comparatively analyze fiscal policy in contemporary Indonesia and the fiscal policy implemented during the era of Prophet Muhammad (SAW), identifying shared principles and potential integrations of Islamic fiscal values into modern governance. Employing a qualitative-descriptive approach with library research, primary data were derived from the Qur’an, authentic Hadith, and classical fiqh sources (e.g., Al-Mughni, Al-Ahkam al-Sultaniyyah), while secondary data included government documents (APBN 2025 Framework, BKF Reports 2024), and peer-reviewed journals (2020–2025). Findings indicate that both systems share core objectives economic stabilization, equitable income distribution, and public welfare enhancement—yet differ significantly in legal foundations (positive law vs. divine revelation), revenue instruments (taxes/PNBP vs. zakat, jizyah, kharaj, fay’), and accountability mechanisms (institutional audit vs. li Allāh wa li al-nās spiritual oversight). Notably, values such as ‘adl (justice), amanah (trustworthiness), transparency, and maslahah ‘ammah (public interest) from the Prophetic fiscal model offer ethical enrichment for Indonesia’s fiscal governance. The study concludes that integrating these values through progressive taxation, zakat–APBN synergy, digital hisbah, and productive waqf can strengthen fiscal legitimacy, social equity, and moral accountability without replacing the existing system.Keywords : fiscal policy, Islamic economics, Prophet Muhammad (SAW), Baitul Mal, APBN